Analisis Penerapan Pengendalian terhadap Produk Kafalah PT. Jaminan Pembiayaan Askrindo Syariah - Fadya Hanin; Fauzi Arif Lubis (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstrak     Analysis of the Implementation of Risk Control on financing kafalah products at PT. Askrindo Syariah Financing Guarantee". This is the result of a qualitative research that aims to answer questions about the risks that exist in financing kafalah products and how to control risks in financing kafalah products at PT. Askrindo Syariah Financing Guarantee. This research uses a case study approach to the research object. Data collection was carried out by way of direct interviews with staff in the operational field, staff in the financial sector and the head of the Medan sharia marketing office (KPS) and supported by documentation related to research.The collected data were analyzed using a qualitative descriptive analysis method.The results obtained were The risks faced by PT Askrindo Syariah Financing Guarantee in financing kafalah products include operational risk, market risk, claims risk and lawsuit risk. will affect the level of profitability PT.JPAS. Control carried out by PT. JPAS, namely with several policies to reduce losses including setting KPS guarantee limits, analysis of surety bond submissions, and maintenance. It is necessary to apply risk management based on sharia principles where apart from guaranteeing and expecting profit, the application of sharia principles is necessary for mutual benefit between the two parties (guarantor and guaranteed).keywords: implementation, control, Askrindo Syariah financing